Necrophilous beetles diversity (Coleoptera: Scarabaeidae, Silphidae, Staphylinidae and Trogidae) in a semiarid area of Zapotitlán de las Salinas valley, Puebla, Mexico - Jiménez Sánchez, Esteban; Quezada García, Roberto; Padilla Ramírez, Jorge (Revista de Biología Tropical, 2013)
Mexico is constituted of arid and semiarid areas in more than half of its land extension, where most of their resources are available only during the rainy season. For those species that recycle resources, such as the carrion fauna, this represents a highly active season; however, the biological and diversity patterns of carrion fauna are poorly understood in these areas. Here, we studied the abundance, diversity and richness of the Scarabaeidae, Silphidae, Staphylinidae and Trogidae families in the Zapotitlán de las Salinas Valley in Puebla, Mexico. Over a one-year period, monthly samples were collected from five different vegetation systems that included the scrublands, a columnar cactus landscape, and altered vegetation. Samples were collected with the use of NTP-80 traps baited with squid, and data on abundance and richness were obtained and evaluated, with respect to monthly precipitation and sampling site location. We collected a total of 613 insects from 12 genera and 15 species. Across systems, Staphylinidae showed the greatest richness (nine species) and abundance (74.2%), followed by Scarabaeidae (21.9%), Silphidae (2.9%) and Trogidae (1%). Significant differences were observed between sites and months; nevertheless, no relationship was observed between abundance and temperature or precipitation. Across taxonomic groups, abundance and richness were most evident for scrub sites, while a greater abundance during the dry season was obtained. The results of this study indicated that the carrion faunal community composition is closely related to the type of vegetation and did not depend on the rainy season. In spite that lesser carrion fauna was observed in this area when compared to other regions of Mexico, this report constitutes a significant contribution to our understanding of the ecological role of this fauna in arid areas.